Rancang Bangun Aplikasi Android ‘GKI Pasteur’ Menggunakan Framework Flutter - Joshua Suherlan; Teddy Marcus Zakaria (STMIK IKMI Cirebon, 2021)
Abstract- The Covid-19 pandemic has been going on since March 2020, social restrictions were imposed by the government through Government Regulation No.21 of 2020. to prevent the spread from spreading and accelerate the handling of Covid-19. Limited public places, one of which is a means of worship. Christian religious services, namely the church as a place of worship, gathering, praying for the congregation is usually done on Sundays and other days. Due to these social restrictions, the number and age of congregations who gather are limited. Given the large number of church congregants, especially GKI Pasteur, it is not possible to gather at the same time as before the pandemic. The GKI Pasteur worship activities are still being carried out online, and will be added onsite by paying attention to the Health Protocol. The delivery of information to the congregation during online-onsite worship, registration for offline worship, church news, and other information is done through social media. To improve services and reach the congregation, an Android-based mobile application was designed to integrate GKI Pasteur's information on social media, websites, and other church news. Registration for onsite worship also becomes transparent so that the congregation is certain whether they are allowed to enter onsite worship or not. Abstrak- Pandemi Covid-19 sudah berlangsung sejak Maret 2020, pembatasan sosial diberlakukan oleh pemerintah melalui PP No.21 tahun 2020. untuk mencegah penyebaran semakin meluas dan mempercepat penangan Covid-19. Tempat-tempat umum dibatasi, salah satunya sarana ibadah. Sarana Ibadah agama Kristen, yaitu gereja menjadi tempat beribadah, berkumpul, berdoa bagi jemaatnya biasa dilakukan pada hari Minggu dan hari lainnya. Karena pembatasan sosial ini, jumlah dan usia jemaat yang berkumpul dibatasi. Mengingat jumlah jemaat gereja, khususnya GKI Pasteur banyak, sehingga tidak memungkinkan untuk berkumpul dalam waktu bersamaan seperti sebelum pandemi. Kegiatan ibadah GKI Pasteur, masih dilakukan secara online, dan akan ditambah secara onsite dengan memperhatikan Protokol Kesehatan. Penyampaian informasi kepada jemaat waktu ibadah onlie-onsite, pendaftaran ibadah onsite, berita jemaat, dan informasi lainnya dilakukan melalui media sosial. Untuk meningkatkan layanan dan menjangkau jemaat dirancang sebuah aplikasi bergerak berbasis Android untuk mengintegrasikan informasi GKI Pasteur yang ada di medsos, website, warta gereja lainnya. Pendaftaran ibadah onsite pun, menjadi transparan sehingga jemaat mendapat kepastian boleh masuk ibadah onsite atau tidak.